Cesarean birth decision-to-delivery interval in sub-Saharan Africa: A systematic review and meta-analysis (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Globally, in 2017, 810 women died daily from pregnancy- or childbirth-related preventable complications. Of these deaths, 94% occurred in resource-poor countries, with the highest maternal and perinatal mortality occurring in sub-Saharan Africa (SSA). We conducted a systematic review and meta-analysis of studies on the decision-to-delivery interval (DDI) from the SSA to determine the mean DDI, establish the maternal and neonatal outcomes reported, and evaluate the obstacles to achieving the gold standard DDI of ≤30 minutes.Methods: We performed a systematic literature review and meta-analysis of eligible studies between January 1995 and December 2022, in seven databases and grey literature. Studies of any design were included if they reported obstetric emergencies delivered by cesarean birth and had information on the DDI. Three independent reviewers applied eligibility criteria, assessed the risk of bias, and extracted data. The authors performed meta-analysis of mean DDI on studies with adequate data. Results: Thirty-nine studies with 41 datasets (12,835 participants), qualified for inclusion. In these studies, only 6.34% of cesarean deliveries were performed in under 30 minutes. A meta-analysis of 27 datasets found an overall DDI mean of 2.81 hours (168.8 minutes, 95%CI 151.5 to 186.2)). The pooled perinatal and maternal case fatality rates for the included studies were 61.2 in 1000 and 444.1 in 100,000 CDs, respectively. Conclusion: This review and meta-analysis found unacceptably high mean DDI, and perinatal and maternal mortality following cesarean delivery in SSA.